A Study on the Compensation Strategies Used to Motivate Employees By Public and Private Banks: Examining the Impact of Compensation Strategies on Employee Motivation and Job Satisfaction in Public and Private Banks (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Businessstrategy associated with rewards and motivation towards job satisfaction hasresilient effect on success of the organization. The connections betweenrewards, motivation and job satisfaction of employees are strategicallysignificant to the success of public and private organizations. Economicrewards are most important to private sector employees. Only limitedresearchers have found no significant differences in the opposite direction.